Absence of MMF1 disrupts heme biosynthesis by targeting Hem1pin Saccharomyces cerevisiae. Issue 12 (10th October 2021) - Whitaker, Gregory H.; Ernst, Dustin C.; Downs, Diana M.
Abstract: The RidA subfamily of the Rid (YjgF/YER057c/UK114) superfamily of proteins is broadly distributed and found in all domains of life. RidA proteins are enamine/imine deaminases. In the organisms that have been investigated, lack of RidA results in accumulation of the reactive enamine species 2‐aminoacrylate (2AA) and/or its derivative imine 2‐iminopropanoate (2IP). The accumulated enamine/imine species can damage specific pyridoxal phosphate (PLP)‐dependent target enzymes. The metabolic imbalance resulting from the damaged enzymes is organism specific and based on metabolic network configuration. Saccharomyces cerevisiae encodes two RidA homologs, one localized to the cytosol and one to the mitochondria. The mitochondrial RidA homolog, Mmf1p, prevents enamine/imine stress and is important for normal growth and maintenance of mitochondrial DNA. Here, we show that Mmf1p is necessary for optimal heme biosynthesis. Biochemical and/or genetic data herein support a model in which accumulation of 2AA and or 2IP, in the absence of Mmf1p, inactivates Hem1p, a mitochondrially located PLP‐dependent enzyme required for heme biosynthesis. Abstract : Lack of the RidA homolog Mmf1p in Saccharomyces cerevisiae results in in vivo persistence of 2‐aminoacrylate and/or 2‐iminopropanoate derived from serine. The reactive intermediates attack and covalently inactivate a portion of the Hem1p population, resulting in a decreased synthesis of heme in mmf1Δ strains.